2012
DOI: 10.1111/j.1752-7325.2012.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Examiner reliability of fluorosis scoring: a comparison of photographic and clinical examination findings

Abstract: Objective To assess and compare examiner reliability of clinical and photographic fluorosis examinations using the Fluorosis Risk Index (FRI) among children in the Iowa Fluoride Study (IFS). Methods The IFS examined 538 children for fluorosis and dental caries at age 13 and obtained intra-oral photographs from nearly all of them. To assess examiner reliability, duplicate clinical examinations were conducted for 40 of the subjects. In addition, 200 of the photographs were scored independently for fluorosis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“… and Cruz‐Orcutt et al . found only moderate agreement (Kappa = 0.48 and 0.46, respectively) between two methods suggesting that the photographic method detects significantly more DDE than the clinical examination method.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“… and Cruz‐Orcutt et al . found only moderate agreement (Kappa = 0.48 and 0.46, respectively) between two methods suggesting that the photographic method detects significantly more DDE than the clinical examination method.…”
Section: Introductionmentioning
confidence: 93%
“…The photographic method may facilitate blinded examinations to avoid observer bias and enable repeated examinations by multiple researchers even remote from the study site . Most studies have demonstrated a high reliability of photographic methods for assessing DDE with high intra‐ and inter‐examiner reliability although one study reported a relatively lower inter‐examiner reliability .…”
Section: Introductionmentioning
confidence: 99%
“…21 New research has been developed out in order to establish new methodologies and protocols in epidemiological surveys, 23 aiming to improve diagnosis using photographs. Some studies 6,18 conclude that the method using photographs is more reproducible and reliable than clinical examinations and can be used to diagnose dental fluorosis.…”
Section: Resultsmentioning
confidence: 99%
“…In another study conducted to assess dental fluorosis by digital photography using T-F index criteria, inter-examiner reliability ranged between 0.4-0.713. In other studies, investigators have tried to compare different indices for assessment of dental fluorosis or to develop different methods for assessment of dental fluorosis and the kappa values were found to range between 0.5 to 11415.…”
Section: Discussionmentioning
confidence: 99%